Protein nanocoatings on synthetic polymeric nanofibrous membranes designed as carriers for skin cells - Bacakova, Marketa; Pajorova, Julia; Stranska, Denisa; Hadraba, Daniel; Lopot, Frantisek; Riedel, Tomas; Brynda, Eduard; Zaloudkova, Margit; Bacakova, Lucie (International journal of nanomedicine, 2017)
Protein-coated resorbable synthetic polymeric nanofibrous membranes are promising for the fabrication of advanced skin substitutes. We fabricated electrospun polylactic acid and poly(lactide-co-glycolic acid) nanofibrous membranes and coated them with fibrin or collagen I. Fibronectin was attached to a fibrin or collagen nanocoating, in order further to enhance the cell adhesion and spreading. Fibrin regularly formed a coating around individual nanofibers in the membranes, and also formed a thin noncontinuous nanofibrous mesh on top of the membranes. Collagen also coated most of the fibers of the membrane and randomly created a soft gel on the membrane surface. Fibronectin predominantly adsorbed onto a thin fibrin mesh or a collagen gel, and formed a thin nanofibrous structure. Fibrin nanocoating greatly improved the attachment, spreading, and proliferation of human dermal fibroblasts, whereas collagen nanocoating had a positive influence on the behavior of human HaCaT keratinocytes. In addition, fibrin stimulated the fibroblasts to synthesize fibronectin and to deposit it as an extracellular matrix. Fibrin coating also showed a tendency to improve the ultimate tensile strength of the nanofibrous membranes. Fibronectin attached to fibrin or to a collagen coating further enhanced the adhesion, spreading, and proliferation of both cell types.
Keywords: Collagen; extracelulární matrix; Cells, Cultured; lidé; skin-tissue engineering; tkáňové podpůrné struktury; Cell Adhesion; Cell Proliferation; Tissue Engineering; keratinocyty; tkáňové inženýrství; fibroblasty; skin cells; nanofibers; kultivované buňky; pevnost v tahu; Humans; buněčná adheze; proliferace buněk; fibronektiny; kolagen; Polymers; collagen; nanovlákna; Tensile Strength; polymery; Fibroblasts; Extracellular Matrix; Keratinocytes; Tissue Scaffolds; fibrin; Nanofibers; Fibronectins; Fibrin; nanocoating